Nosocomial infective endocarditis in a renal transplant patient: culprit central venous line - Alhomayeed, Bader; Bhat, Abdul Wahid; Manzoor, Adil; Al-hamedy, Khalid (International Journal of Advances in Medicine, 2017)
Nosocomial infective endocarditis (IE) is a relatively uncommon but, a serious complication affecting critically ill hospitalized patients who are frequently exposed to life-saving invasive procedures. Immunosuppressive treatment in solid organ transplant recipients predisposes to infections, nevertheless, nonspecific symptoms of IE, such as fever, lassitude, weight loss, and signs of inflammation may often be misinterpreted as acute rejection episode or a common urinary tract infection. The case reported here was a recent renal transplant with methicillin-resistant Staphylococcus aureus IE. We believe the diagnoses of IE in her were missed at her first presentation due to her non-specific symptoms and lack of echocardiography and blood culture results. Septic procedure at insertion of central venous catheter (CVC) in the Intensive Care Unit with trauma to tricuspid valve (TV) at the time of CVC insertion was a possible source of infection for IE. The patient was managed effectively with intravenous antibiotics in spite of having hanging pedunculated vegetation on TV.